The Influence of Corporate Governance, Capital Structure, and Profitability on Firm Value in Banking Sector in Indonesia - Hidayat, Gustina; Affandi, Azhar; Anwar, Mokhamad (IJBLE Scientific Publications Community Inc., 2025)
This study investigates the influence of corporate governance, capital structure, and profitability on firm value in the Indonesian banking sector. Using a quantitative research design, data were collected from publicly listed banks’ financial reports and analyzed through multiple regression. Results indicate that corporate governance and profitability positively impact firm value, while high capital structure negatively affects it. Control variables, such as bank size and liquidity, also show significant relationships. These findings highlight the importance of robust governance, prudent debt management, and operational efficiency for sustainable growth. The study offers practical insights for managers, regulators, and investors while addressing limitations for future research.